2019
DOI: 10.2116/analsci.19p119
|View full text |Cite
|
Sign up to set email alerts
|

Gibbs Transfer Energies of Ions from a Mixed Solvent of 2H,3H-Decafluoropentane and 1,2-Dichloroethane to Water

Abstract: The transfer of hydrophilic, lipophilic, and fluorophilic ions at the interface between water (W) and a mixed solvent (MIX) of 2H,3H-decafluoropentane (DFP) and 1,2-dichloroethane (DCE) was studied voltammetrically and potentiometrically, and the formal Gibbs transfer energies of the ions from MIX to W, ΔG 0 tr, ′ MIX→W, were determined. The ΔG 0 tr, ′ MIX→W values of all the ions tested were higher than those from DFP to W. Namely, the ions would exist more stably in MIX than DFP, even for fluorophilic ions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Hence, the Gibbs energies for the migration of the ion pair Fc + A − (Δ G (Fc + A − ) DCE→H 2 O ) can be tuned by the Gibbs energy for phase migration of added anion (Δ G (A − ) DCE→H 2 O ) on the basis of eqn (4). 54 Δ G (Fc + A − ) DCE→H 2 O = Δ G (Fc + ) DCE→H 2 O + Δ G (A − ) DCE→H 2 O …”
Section: Resultsmentioning
confidence: 99%
“…Hence, the Gibbs energies for the migration of the ion pair Fc + A − (Δ G (Fc + A − ) DCE→H 2 O ) can be tuned by the Gibbs energy for phase migration of added anion (Δ G (A − ) DCE→H 2 O ) on the basis of eqn (4). 54 Δ G (Fc + A − ) DCE→H 2 O = Δ G (Fc + ) DCE→H 2 O + Δ G (A − ) DCE→H 2 O …”
Section: Resultsmentioning
confidence: 99%
“…In fact we could obtain valuable information for understanding the characteristic intermolecular interactions of fluorous molecules. that were previously reported for 14 fluorinated anions [7][8][9] (however, the data for an anion, 2, have been revised). The corresponding values for 12 non-fluorinated cations [7][8][9] and 16 non-fluorinated anions 7,9 are shown in Tables S1 and S2 (Supporting Information).…”
Section: -4 -mentioning
confidence: 97%
“…In previous papers, [6][7][8][9] our group reported the applicability of a fluorous solvent, DFP (2H,3H-or 1,1,1,2,3,4,4,5,5,5-decafluoropentane), as a non-aqueous solvent for liquidliquid electrochemistry. Using the polarized DFP/water (W) interface, the apparent or formal Gibbs energies 10 were then compared with those from W to non-fluorinated organic solvent such as nitrobenzene (NB) and 1,2-dichloroethane (DCE).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we have reported that an mixed solvent consisting of DFP and DCE becomes a useful solvent for extraction of a highly fluorinated ion compared to DCE. 10 However, DFP's boiling point is as low as 66ºC, and its volatilization often made the experiment difficult. Therefore, other fluorous solvent, especially low volatile one, would be desirable.…”
Section: Introductionmentioning
confidence: 99%
“…were listed inTable 2together with the reported values of the formal Gibbs transfer energy for DFP, Although the estimated values of G 0 tr ' ,F→W might be affected by the ionpair formation in the F phase, the values still seem to be useful as a quantitative measure of the affinity of ions for the fluorous solvent 6,9,10. TheFigure5 shows the plots of G 0 tr ' ,F→W for TFE (triangle) and OFE (square), against G 0 tr ' ,DCE→W .…”
mentioning
confidence: 99%